Method to improve charging power quality of electric vehicles. Issue 16 (18th December 2018) - Li, Fucun; Guo, Liang; Liu, Lijun; Li, Xiao; Wang, Qing
Abstract : With the increasing number of electric vehicles, the vehicle‐to‐grid (V2G) technology has become a hotspot for the present research because it can cause peak‐load shifting; it is also a practical technical means to improve the power grid capacity of new energy absorption in the field of new energy access to grid. In the interaction between electric vehicle and power grid, its bidirectional AC/DC transform control is mostly pulse width modulation control; large amplitude fluctuations will cause damage to AC/DC converters and electric vehicle batteries when electric vehicles are connected to these intermittent new energy sources (such as wind, tidal energy etc.). In order to solve these problems, from the system point of view, the authors combine the theory of instantaneous reactive power and introduce a virtual coordinate system, reduced the impact of volatile energy and improve the power quality of electric vehicle charging; finally, the feasibility of the method is verified by simulation.